Optical solitons to the nonlinear Shrodinger's equation with spatio-temporal dispersion using complex amplitude ansatz - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi (Taylor & Francis Ltd, 2017)
In this work, we investigate the optical solitons to the non-linear Shrodinger's equation with spatio-temporal dispersion. There are two types of non-linear media studied in this paper. They are Kerr law and parabolic law. By adopting a complex amplitude ansatz method composed of the addition of bright and dark optical solitons, we present the exact dark, bright and dark-bright or combined optical solitons to the model. Numerical results and discussions are also presented.
Keywords: Kerr law; parabolic law; optical soliton